Study on Operating Temperature Prediction Model of Aero High-speed Gears - Chen Yuling; Zhu Jiazan; Chen Taimin; Zhu Caichao; Wei Peitang; Xu Yongqiang (Jixie chuandong)
With the continuous improvement of the operating temperature of aero transmission under the high-speed and high load, gear scuffing failure has become a key factor restricting the performance of aircrafts. To efficiently predict the operating temperature of aero gears, a sequential coupling numerical analysis method of the gear temperature is proposed for an aero engine gear, which simulates the bulk temperature and flash temperature under different working conditions, considering factors such as solid-liquid-gas multi-state flow heat exchange and heat dissipation coefficients of different tooth surfaces. The simulated gear contact temperature is compared with calculation results of ISO/TS 6336-20 and shows consistency, the largest deviation between which under different working conditions is controlled within 10%. When the input speed is 22 400 r/min and the torque is 119.4 N<alternatives>∙ <?fx-imagestate width="1.86266661" height="2.62466669"?> <?fx-imagestate width="1.86266661" height="2.62466669"?> </alternatives>m, the split large gear contact temperature reaches 242.6 ℃, the scuffing safety factor is 1.22, and there is a risk of scuffing failure. The proposed simulation analysis method can effectively predict the operating temperature of aero high-speed gears, and provide an efficient and reliable method for assessing the risk of aero gear scuffing failure.